Penerapan Metode Simpleks untuk Optimasi Prestasi Belajar Siswa di MIN 2 Oku - Husniawati, Husniawati; Areska, Finta; Sandra, Nazua Adi; Agustino, Ringgho; Sunan, Sunan; Destiarini, Destiarini (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to apply the Simplex method within the framework of operations research to optimise the distribution of student learning time at MIN 2 OKU, particularly in Mathematics, Indonesian Language, and Science subjects, which have different levels of difficulty. The research uses a quantitative approach with a mathematical modelling design based on Linear Programming. Data was obtained through observation of student learning activities, interviews with teachers, distribution of questionnaires to students, and documentation of learning outcomes as the basis for determining the objective function and model constraints. The collected data was analysed by constructing a mathematical model, which was then solved using the Simplex method to obtain the optimal solution. The results of the analysis show that the most optimal allocation of learning time is 2 hours for Mathematics, 0.5 hours for Indonesian Language, and 0.5 hours for Science. These findings provide an objective picture of more efficient and proportional learning time management according to student needs. Thus, the Simplex method has been proven to be effectively applicable in the context of primary education as a data-based decision-making tool to support more focused and rational learning planning.